The Relationship Between Hypoadiponectinemia and Cardiovascular Events in Liver Transplant Recipients. Issue 11 (November 2019) - Siddiqui, Mohammad Bilal; Patel, Samarth; Arshad, Tamoore; Lee, Emily; Albhaisi, Somaya; Driscoll, Carolyn; Wolver, Susan; Reichman, Trevor; Bhati, Chandra; Siddiqui, Mohammad Shadab
Abstract : Background: Cardiovascular disease (CVD) is an important cause of morbidity and mortality after liver transplantation (LT). Serum adiponectin levels inversely correlate with CVD-related outcomes, but the relationship between hypoadiponectinemia and CVD after LT is unknown. Thus, the aim of the present study was to prospectively evaluate this relationship in LT recipients (LTR). Methods: LTR were prospectively enrolled (N = 130) between January 1, 2012, and January 1, 2014. Baseline adiponectin levels were drawn at enrollment and patients were followed for CVD events. Hypoadiponectinemia was defined as serum adiponectin <10 µg/mL. The primary endpoint was a composite CVD outcome consisting of myocardial infarction, angina, need for coronary revascularization, stroke, or cardiac death. Results: The mean age was 58 ± 11 years and prevalence of obesity, diabetes, and dyslipidemia was 40%, 35%, and 40%, respectively. A total of 20 CVD events were noted, after median follow up of 45 months. Hypoadiponectinemia was significantly associated with future risk of CVD events (hazard ratio, 3.519; 95% confidence interval, 1.180-10.499, P = 0.024). This association was independent of traditional CVD risk factors including age, gender, obesity, hypertension, diabetes, and choice of immunosuppression. Conclusions: Hypoadiponectinemia is a strong independent predictor of future cardiovascular events in LTR, which can be incorporated in clinical practice to assess CVD risk assessment after LT.